Neutrophil extracellular trap-associated RNA and LL37 enable self-amplifying inflammation in psoriasis - Herster, Franziska; Bittner, Zsofia; Archer, Nathan K.; Dickhöfer, Sabine; Eisel, David; Eigenbrod, Tatjana; Knorpp, Thomas; Schneiderhan-Marra, Nicole; Löffler, Markus W.; Kalbacher, Hubert; Vierbuchen, Tim; Heine, Holger; et al. (Nature Communications, 2020)
Antimicrobial peptide LL37 can bind nucleic acids and potentiate their sensing by endosomal TLRs. Here the authors show that LL37 binds to RNA from neutrophil extracellular traps (NETs), which amplifies inflammation and production of more LL37 and NETs via TLR8/13, suggesting that LL37 contribution to psoriasis may be fueled by NET-associated RNA.
Gesehen am 03.04.2020